Applying information visualization on centre for Islamic Thought and Understanding (CITU) website using rooms technique / Mus Alimin Mohd Shah - Mohd Shah, Mus Alimin (Faculty of Computer and Mathematical Sciences, 2007)
The research of this project is about Applying Information Visualization on Centre for Islamic Thought and Understanding (CITU) Website Using Rooms Technique. The objectives of this research project are to evaluate the user interface of CITU website, to identify the characteristics of Rooms technique, and to demonstrate the use of Rooms technique to CITU website. The researcher uses three approaches in order to gather information about Information Visualization especially about Rooms technique. The researcher uses the questionnaire as the first approach to evaluate the current CITU website user interface and second, the comparison of Information Visualization technique table. Lastly, this research acquires the evaluation of the new CITU website after using Rooms technique. Thus, the researcher is capable to identify the appropriate information about Rooms technique. After that the researcher will apply the information visualization to the website and hence, the entire objective has been successfully achieved.